STRATEGI PEMASARAN PRODUK TALANGAN UMRAH DAN HAJI FURODA PADA PT. TANUR MUTMAINATUN KANDANGAN - Awalia, Hushila (JURNAL EKONOMI DAN BISNIS (EKOBIS-DA), 2023)
Abstract Travel Tanur mutmainatun is one of the travel engaged in the field of Umrah and Hajj Furoda. The travel was established in 2016 and has many pilgrims spread across various regions of South Kalimantan. The products offered also have bailouts for Umrah so that many are interested in Umrah by going first to pay later. From year to year there has been an increase in public interest to go for Umrah and Hajj with PT Tanur Muthmainnatun Travel, so that in 2018 PT Tanur Muthmainnatun Travel has 230 branches throughout Indonesia. Therefore, this study wants to know what strategy is used by PT Tanur Muthmainnatun's Travel. In this study we want to know the theory put forward by Kotler and Keller regarding the marketing mix which is divided into 4Ps (product, promotion, price, place) to discuss the marketing strategy of Umrah and Hajj furoda products at PT Tanur Muthmainnatun's Travel. This study aims to determine the marketing strategy used by PT Tanur Muthmainnatun to increase the number of pilgrims. This research is a qualitative descriptive research or field research, which uses observation, interview, and documentation methods. Based on research conducted by PT Tanur Muthmainnatun's travel marketing strategy to increase the number of pilgrims using several ways, namely by placing advertisements on social media such as instragram and facebook, directly involved in visiting prospective pilgrims, and distributing brochures directly through PT Tanur Muthmainnatun's official travel partners. The results showed that, first, PT Tanur's marketing strategy applies four things, namely: (1) Products, by providing diverse and quality products and materials (2) Price, by offering affordable prices, (3) Promotion, by advertising products through social media, such as on instragram, facebook and marketing directly to potential customers. (4) Place, by choosing a location that is easily strategic. Keywords: marketing strategy, umrah haji furoda, PT. Mutmainatun furnace